Kernel Estimation Techniques for the Analysis of Clinical Curves - Müller, H.-G.; Ihm, P. (Methods of Information in Medicine, 1985)
Kernel estimation procedures for the comparison of samples of longitudinal clinical curves are discussed. We show how samples of curves can be compared by means of “empirical parameters” and how a typical longitudinal curve can be defined by “longitudinal averaging”. This method allows to summarize the information in a sample of monotonous curves and to derive local confidence bands for the longitudinal mean curve. Under specific assumptions, this procedure is strongly consistent.As an example, we analyze and compare the long-term behavior of two types of heart pacemakers. Special consideration is given to the practically relevant choice of kernels and of bandwidths (smoothing parameters).
Keywords: Kernel Estimators; Nonparametric Regression; Longitudinal Averaging; Empirical Parameters; Bandwidth Selection; Long-Term Behavior of Heart Pacemakers